Soluble Epoxide Hydrolase Plays a Vital Role in Angiotensin II-Induced Lung Injury in Mice. Issue 5 (November 2018) - Tao, Wei; Li, Ping-Song; Xu, Gang; Luo, Yi; Shu, Yu-Sheng; Tao, Yong-Zhong; Yang, Liu-Qing
ABSTRACT: Background: Angiotensin II plays a vital role in the pathogenesis of acute respiratory distress syndrome (ARDS). However, its mechanism is not well defined. Angiotensin II upregulates the expression of soluble epoxide hydrolase (sEH; Ephx2). sEH is suggested as a potential pharmacologic target for ARDS. The present study investigates whether the sEH is involved in the angiotensin II-triggered pulmonary inflammation and edema using an angiotensin II-induced lung injury animal model. Methods: Lung injury was induced by angiotensin II intratracheally instillation in wild-type or Ephx2 deficient mice. Results: sEH activities were markedly increased in wild-type mice treated with angiotensin II. Angiotensin II markedly increased the levels of tumor necrosis factor-α and interleukin-1β in bronchoalveolar lavage fluid, worsened alveolar capillary protein leak and lung histological alterations, and elevated activity of activator protein-1 and nuclear factor-κB. However, these changes were significantly improved in Ephx2 deficient mice. Moreover, Losartan, an angiotensin II receptor 1 antagonist, abolished the sEH induction and improved mortality. Conclusions: Angiotensin II-induced lung injury was improved in sEH gene deleted mice. The angiotensin II-triggered pulmonary inflammation is mediated, at least in part, through the sEH.